RADIATION CONTROL DURING THE CONSTRUCTION OF THE OLYMPIC FACILITIES IN SOCHI CITY - I. K. Romanovich; K. A. Saprykin (Радиационная гигиена)
This paper presents data on the organization and results of the provision of the radiation safety in the period of preparation for the Winter Olympic and Paralympic games in Sochi, 2014. The following topics are overviewed in the paper: allocation of land plots for construction of the Olympic facilities; organization of the sanitary surveillance of the imported equipment, construction materials and designs for the construction of the Olympic facilities; putting the Olympic venues into operation. Dose rate of gamma radiation at all land plots, which were allocated for the construction of the Olympic facilities, conformed to the requirements of sanitary regulations. The average dose rate of gamma radiation was 0.11 μSv h-1 in the Coastal cluster and 0.14 μSv h-1 in the Mountain cluster. The radon fluence rate from the ground surface exceeded the prescribed limit of 80 mBq m-2 s-1 only at the land plot allocated for construction of the «House of receiving official delegations «Achipse» and the «House of receiving official delegations «Psekhako» in the Mountain cluster. The maximal value of 188 mBq m-2 s -1 was registered here. The buildings projects for this area included using radon protection measures, which were implemented during the construction.